The Diverse Subjects of Early Childhood Parenting Education - Vanessa Schwenker (Social Work and Society)
Drawing on ethnographic data, this article analyzes differentiation within a German parenting education program, illustrating how those involved become subjects of parenting education and how these practices shape diversity as practices of recognition. The study adopts Rose and Ricken's (2018) conceptualization of recognition as (re-)addressing, moving beyond a normative understanding of recognition as affirmation and delving into differentiation at the levels of selection, norm formation, positioning, and valuation. The study underscores the ambivalent nature of diversity practices and reveals a nuanced hierarchy within the program, where role modelling and a 'makeover' narrative drive the relational dynamics and shape the position of the 'professional other' (Heite, 2008) as a 'diversity worker' (Ahmed, 2012). Ultimately, the study concludes that diversity practices are inherently situated within societal dynamics of power and constitute powerful practices of recognition themselves, rather than serving as a means of escaping from power.